Neuroinflammation and Virus Replication in the Spinal Cord of Simian Immunodeficiency Virus–Infected Macaques. Issue 1 (January 2015) - Mangus, Lisa M.; Dorsey, Jamie L.; Laast, Victoria A.; Hauer, Peter; Queen, Suzanne E.; Adams, Robert J.; McArthur, Justin C.; Mankowski, Joseph L.
Abstract : Abstract: Studies of neurologic diseases induced by simian immunodeficiency virus (SIV) in Asian macaques have contributed greatly to the current understanding of human immunodeficiency virus pathogenesis in the brain and peripheral nervous system. Detailed investigations into SIV-induced alterations in the spinal cord, a critical sensorimotor relay point between the brain and the peripheral nervous system, have yet to be reported. In this study, lumbar spinal cords from SIV-infected pigtailed macaques were examined to quantify SIV replication and associated neuroinflammation. In untreated SIV-infected animals, there was a strong correlation between amount of SIV RNA in the spinal cord and expression of the macrophage marker CD68 and the key proinflammatory mediators tumor necrosis factor and CCL2 . We also found a significant correlation between SIV-induced alterations in the spinal cord and the degree of distal epidermal nerve fiber loss among untreated animals. Spinal cord changes (including elevated glial fibrillary acidic protein immunostaining and enhanced CCL2 gene expression) also were present in SIV-infected antiretroviral drug–treated animals despite SIV suppression. A fuller understanding of the complex virus and host factor dynamics in the spinal cord during human immunodeficiency virus infection will be critical in the development of new treatments for human immunodeficiency virus–associated sensory neuropathies and studies aimed at eradicating the virus from the central nervous system.